Enrichment Geological Conditions and Resource Evaluation Methods for the Gas in Thinly Interbedded Coal Measures: A Case Study of the Chengzihe Formation in the Jixi Basin - Jiangpeng Guo; Shu Tao; Caiqin Bi; Yi Cui; Bin Yu; Yijie Wen (Energies)
The Cretaceous Chengzihe Formation in the Jixi Basin hosts abundant coal measure gas resources. Analyzing the geological conditions for gas enrichment and evaluating its resource potential are essential for advancing unconventional gas exploration. However, studies on the geological conditions controlling the enrichment of thinly interbedded coal measure reservoirs in the Chengzihe Formation and corresponding assessment methods remain lacking. Based on the analysis of source–reservoir–seal characteristics of the thinly interbedded coal measure gas system in the Jixi Basin, integrated with resource assessment and reservoir formation controls, this study systematically reveals the enrichment patterns and accumulation mechanisms. The results show that the accumulation of thinly interbedded coal measure gas depends on three key geological factors: the gas-generating capacity of high-quality source rocks, the widespread distribution and stacking of thinly interbedded reservoirs, and the sealing capacity of cap rocks. In addition, enrichment is influenced by multiple factors, including tectonic evolution history, magmatic intrusion, sedimentary microfacies, and hydrogeological processes. Among these, the development of sedimentary microfacies (interdistributary bay and peat swamp) plays a decisive role in controlling the spatial distribution and physical properties of the reservoirs, while other factors further shape gas enrichment through synergistic interactions. Finally, using the volumetric method, the estimated gas resources of thinly interbedded coal measure gas in the Chengzihe Formation are 1226.73 × 108 m3, with the upper member showing significant potential of 688.98 × 108 m3.